THE EFFECT OF HERRINGBONE TECHNIQUE ON STUDENTS’ READING COMPREHENSION OF THE FIRST YEAR STUDENTS AT SMP NEGERI 23 MAKASSAR - Besse Muliana; Dahlia D. Moelier (Publikasi dan UKI Press UKI Toraja., 2022)
The aim of his research is wanting to know that the herringbone technique application is effective to improve student skill in reading, predict, make the conclusion in every paragraph and able to solving the problem by the students in understand the reading or discourse. This research is experimental research that I did in SMP Negeri 23 Makassar. In this research the total of population in Grade VII students are 480 students that shared in 12 classes. The researcher choose sample in class VII-12 are 32 students. The aim of the researcher to choose class VII12 as a subject of the research because the average of the student in this class still less to understand the reading text. The result data analysis in pre-test and post-test shows up that t-test score is 36.25 and t-table score is 2.036. It means the t-test score is better than t-table or (tt36.25> 2.036). These things show up the students’ skill to understand reading text at the end of the research is improved. These things can identify with the significant different between average score in pre-test (3) and post-test 5.8). This research shows up if herringbone technique that try out in SMP Negeri 23 Makassar is works. It appears that student’s English skill to understand reading text from bad to better.